Role of Grab on the social life changes of Bengkulu City - Afrima Widanti; Dewi Rahmayanti (Journal of Islamic Economics, Management, and Business (JIEMB), 2020)
Purpose – The presence of Grab has invited many discussions. The purpose of this study is to know the role of Grab on changes in social life in Bengkulu city both in terms of Grab drivers, consumers, and other conventional transportation.Method – This study uses a qualitative approach with an in-depth interview method. The total respondents in this study are 38 people consisting of 5 people from Grab drivers, 30 people from consumers, and five people from conventional transportation.Result – This study found that there were changes in Grab drivers' income, but there were no social changes in Grab drivers. On the other hand, there were social changes in Grab consumers and conventional drivers. Implication – This study can be used by public, government, and private sector to understand better consumer behaviour in online transportation field.Originality – As the growth of online transportation in Indonesia is increasing, this study offers early understanding upon the phenomena.